Anti-Hu antibody titre and brain metastases before and after treatment for small cell lung cancer. Issue 3 (1st September 1999) - Verschuuren, Jan J; Perquin, Mark; ten Velde, Guul; De Baets, Marc; Vriesman, Peter van Breda; Twijnstra, Albert
Abstract : OBJECTIVES: To follow up the level of anti-Hu antibody titres during chemotherapy and to compare the pattern of metastases and other neurological complications before and after chemotherapy in patients with small cell lung cancer (SCLC) with and without low titre anti-Hu antibodies. Seventeen per cent of patients with SCLC without paraneoplastic syndromes have a low titre of anti-Hu antibodies in their serum. Previous studies suggested that these antibodies correlate with a more indolent tumour growth. METHODS: The serum of 52 consecutive patients with SCLC were studied before and during chemotherapy, and the correlation with stage of disease and pattern of metastases was examined. All serum samples were investigated using western blot and enzyme linked immunosorbent assay (ELISA) with HuD recombinant protein. All patients with SCLC were investigated using MRI of the brain, CSF, bone marrow aspiration, ultrasound of the abdomen, and radionuclide bone scan. RESULTS: Nine (17%) of 52 SCLC serum samples were positive by western blot. At the time of diagnosis none of the anti-Hu positive patients had either CNS (brain or leptomeningeal), epidural, adrenal, or bone marrow metastases and 56% had limited disease. In eight of 43 anti-Hu negative patients CNS metastases were found at the time of diagnosis, and only 30% had limited disease. The prevalence of bone and liver metastases was similar in both groups. Survival was 11 (SD ) months for the 43 anti-Hu negative and 10 (SD 6) months for the nine anti-Hu positive patients. Male:female ratio in the anti-Hu negative group was 4.4:1, and in the anti-Hu positive group 2:1. CONCLUSIONS: No anti-Hu antibody positive serum, as tested by western blot, became negative during chemotherapy. Anti-Hu positive and anti-Hu negative patients had similar survival, but anti-Hu positive patients tended to be women, had limited disease at the time of tumour diagnosis, and initially metastases seemed to spare the nervous system.